Demography and population structure of Northeastern mediterranean monk seal population - KURT, MERVE; GÜCÜ, ALI CEMAL (Mediterranean Marine Science, 2021)
The Northeastern Mediterranean coasts that border southern Turkey host one of the last strongholds for the survival of the endangered Mediterranean monk seal (Monachus monachus, 1779). The seal colonies inhabiting south coast of Turkey have been studied since 1994 through various short-term research projects focusing on distinct small populations that were thought to be isolated. In this study, the entire extent of the area was monitored approximately for 3 years (between 2015 and 2018) with camera traps places in 20 caves known to be actively used by the seals. A total of 7014 images taken throughout the study period, along with 25,100 images taken previously, were used to identify the seals inhabiting the area. In total, 37 individuals were identified based on the natural marks on the body. Based on photo-identified seals, a mark-recapture method was applied to estimate the total population size within the Northeastern Mediterranean. The overall population size was found to be 46 (SE=7.7) in the case of closed population and 53(SE=34.8) in the case of open population during the study period. The range of identified seals was almost six times larger than previously documented in the same area, reaching distances up to 245 km. The population estimate indicated a decrease in population size compared to previous studies. Finally, the study emphasises the importance of long-term monitoring studies elucidating changes in the demographic parameters in relation to threats posed, rather than cut-paste measurement suggestions which are not applicable in reality, while structuring the conservation actions targeting survival of this highly endangered species.